Heterogeneous marrow uptake on FDG PET/CT is not always a sign of lymphomatous involvement - Arun Reddy Gorla; Bhagwant Mittal; Anish Bhattacharya; Pankaj Malhotra; Subhash Varma (World Journal of Nuclear Medicine)
Heterogeneous patchy marrow uptake on fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) in a histologically proven case of lymphoma is usually considered a virtually pathognomonic sign of lymphomatous involvement. Here, we present a young male patient of T-cell-rich non-Hodgkin lymphoma (NHL), an uncommon morphologic variant of diffuse large B-cell lymphoma (DLBCL), who had undergone three sequential PET/CT scans at our department during the course of his therapy. These images depict the need for careful direct comparison of the current study with the previous PET/CT studies to avoid erroneous interpretation.